Implementasi Algoritma Quicksort Untuk Pembangkitan Kunci Algoritma Elgamal Pada Pengamanan Data File Dokumen - Al-Amansyah Al-Amansyah (Graha Mitra Edukasi, 2022)
A valid document is an important article containing information. Typically, documents are written on paper and the information is written in ink either by hand or using electronic media. For that we need a security system to secure the contents of the documents contained therein. In this research, a cryptographic method is used that will ensure the security of a document file. In this research, there is a security process that uses the Elgamal algorithm method as a solution to the implementation of the Quicksort algorithm method for document files. The results of this study indicate that the visual basic application can determine whether document files are safe or not. Using this method can help by securing the contents of a document file so that it is not known easily. Quicksort implementation that uses the Elgamal algorithm will be implemented using the visual basic application as evidence of the results of securing document files safely